Assessing Social and Economic Impact: A Case Study of the Hafidzpreneur Scholarship Program - Aam Slamet Rusydiana; Nadia Nurul Izza; Mia Sari; Annisa Kartika Ocktavia; Siti Maysyaroh; Siti Salmah (SMART Insight, 2023)
This paper aims to assess the social impact of the Hafidzpreneur scholarship program organized by the Riau Provincial government using Social Return on Investment (SROI) analysis as its main approach. A qualitative approach has been applied to better understand the impacts associated with these projects, while in-depth interviews have been the main tool in data collection. The results of the SROI analysis yielded a ratio of 1:4.2, reflecting that each unit investment of Rp 1 generates a social impact and value of Rp 4.2. This finding reflects the significant positive impact of the program in creating social value that covers multiple dimensions, including financial, social, and spiritual aspects. The findings also suggest that the use of the SROI approach and qualitative methods has provided an in-depth understanding of the impact of the holistic development projects of the Hafidzpreneur scholarship program provided by the Riau Provincial government. The results of this study have strong implications in designing, managing, and measuring the impact of similar programs in the future, as well as in enhancing a broader understanding of the social value generated by organizations for sustainable development.